The impact of preoperative pain-related psychological factors on pain intensity post-surgery in Jordan. (December 2021) - Khalil, Heba; Shajrawi, Abedalmajeed; Dweik, Ghadeer; Zaghmouri, Abeer; Henker, Richard
This study aimed to investigate the impact of preoperative psychological factors on postoperative pain. We included 300 postoperative patients who underwent open reduction and internal fixation surgery. Pain Scale, Pain Catastrophizing Scale, and Depression, Anxiety, and Stress Scale were completed by patients preoperatively and at 24 hours after surgery. Clinical characteristics were obtained from medical records. Data were analyzed using multiple linear regression. Postoperative pain was predicted by pain catastrophizing and anxiety symptoms. High preoperative catastrophizing and anxiety levels were associated with increased pain postoperatively. However, the relationships between preoperative depressive and stress symptoms and postoperative pain were not significant.